Tjukurpa irititja munu kuwaritja = a story of past and present - Thompson, Punch; Nganampa Health Council ([Alice Springs, N.T.] : Nganampa Health Council, 1990)
A poster which reproduces a painting by (Panytju) Punch Thompson which compares pre-European and modern Aboriginal health and living conditions which is titled "Australian burning with sickness". It features the shape of Australia with kangaroos, emu, a goanna, a snake, plants, and symbols painted on it, which is surrounded by dot patterns and text. Enclosed in a border of pale green dots on a black line, and set on a white background. Explanatory text at foot in both English and an Indigenous language.
Caption title.
In Indigenous Australian language, English.
Keywords: Thompson, Punch -- Posters; Nganampa Health Council -- Posters; Aboriginal Australians -- Health and hygiene -- Northern Territory -- Posters; Aboriginal Australians -- Effects of colonization on -- Posters; Aboriginal Australians -- History -- Posters; Aboriginal Australians -- Northern Territory -- Social life and customs -- Posters; Aboriginal Australians -- Alcohol use -- Posters; AIDS (Disease) -- Australia -- Posters; Artists, Aboriginal Australian -- 20th century -- Posters; Posters, Australian; Australia -- Posters; Australian